Daytime births are associated with better perinatal outcomes in secondary and tertiary hospitals. Issue 2 (24th February 2011) - de Jonge, Ank; Twisk, Jos; Hutton, Eileen
Abstract : Commentary on: de Graaf JP Ravelli AC Visser GH . Increased adverse perinatal outcome of hospital delivery at night. BJOG 2010 ;117 :1098 –107 .